2017
DOI: 10.1111/1471-0528.14966
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of infertility in China: a population‐based study

Abstract: In China, 25% of couples actively attempting to become pregnant suffered infertility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
185
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 277 publications
(214 citation statements)
references
References 38 publications
(44 reference statements)
5
185
0
Order By: Relevance
“…Infertility is defined as the inability to conceive for at least 1 year (1). Infertility is a common condition affecting 10-20% of women at the reproductive age across different countries (2,3). Assisted reproductive technology (ART) has allowed millions of infertile couples in the world to conceive successfully since 1978 (4).…”
Section: Introductionmentioning
confidence: 99%
“…Infertility is defined as the inability to conceive for at least 1 year (1). Infertility is a common condition affecting 10-20% of women at the reproductive age across different countries (2,3). Assisted reproductive technology (ART) has allowed millions of infertile couples in the world to conceive successfully since 1978 (4).…”
Section: Introductionmentioning
confidence: 99%
“…Itis estimated that 1 out of 4 couples are infertile [2]. Latest epidemiological investigations have shown prevalence of infertility to be 25% in China [3]. Chromosomal abnormalities were associated with infertility [5] and maybe the major recognized genetic causes for recurrent miscarriage [9].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of infertility is high around the world, it is estimated that 1 out of 4 couples are infertile [2]. The latest epidemiological investigation in China showed that among 10742 women, prevalence of infertility was 25.0% (2680/10742) [3].…”
Section: Introductionmentioning
confidence: 99%
“…[27] However, in discordance with the literature, most of the cases of infertility in the present study sample were of known causes. [28] This might be explained by the possibility of a selection bias given that the study setting may provide treatment for such underlying causes as the ovarian, tubal, or uterine treatable disorders.…”
Section: Discussionmentioning
confidence: 99%